Implementation of Completely Randomized Design (CRD) using R Software to Evaluate Linear Algebra Learning Systems Pasca the Covid-19 Pandemic - Simarmata, Justin Eduardo; Chrisinta, Debora (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
Completely Randomized Design (CRD) is an experimental design that is applied based on treatment control by researchers. In this study, CRD was applied to evaluate the learning system of the Linear Algebra course pasca the Covid-19 pandemic using R Software. The experiment was carried out as many as 2 tests which were categorized as learning group 1 consisting of 28 students and learning group 2 consisting of 29 students. The treatment given is based on the learning system before the Covid-19 pandemic which was carried out face-to-face, during the pandemic which was carried out online and pasca the pandemic which was carried out in a mixed manner (face-to-face and online). The online learning system during the pandemic provides better student learning outcomes than face-to-face or through a blended learning system. However, this must be further evaluated for environmental conditions and learning models so that they can be applied to the learning system pasca the Covid-19 pandemic.